Universal design evaluation of the accessibility of the University of the Philippines Diliman Libraries for users with disabilities - Morpos, Clyde Jeric Joan
Since academic libraries function as the strongholds of knowledge, it is only appropriate that academic libraries are utilized freely so that their benefits will be realized to the maximum capacity. When the status of a national university, the University of the Philippines Diliman is responsible for optimizing library access for all stakeholders, including persons with disabilities (PWDs). Doing so may require the application of universal design, defined as the design of products and environments to be usable by all people, to the greatest extent possible, without the need for adaptation or specialized design. This is the primary concern of the research. Specifically, it asks; 1) how accessible UP Diliman Libraries are in terms of library organization standards and Philippine disability laws and 2) how UD principles can be applied to address the gaps in or to further improve the accessibility of UP Diliman Libraries for PWDs. A qualitative method was employed to gather data through a survey questionnaire accomplish by head librarians and onsite examination or inspection of UP Diliman Libraries. Finding show that UP Diliman Libraries have a moderate level of physical accessibility, a low level of collection accessibility, and a moderate level of service accessibility. Practical applications of UD principles were recommended to improve the accessibility of UP Diliman Libraries for PWDs.